Analisis Berpikir Kritis Siswa Bergaya Kognitif Reflektif dan Impulsif pada Pelajaran Biologi melalui Model Means Ends Analysis (MEA) Menggunakan Media Visual - Nadia Dwi Rochika; Imas Cintamulya (Universitas Sebelas Maret, 2017)
Teachers' learning is mostly presented with conventional models or lectures so that critical thinking has not been the focus of teachers in the learning process as well as with cognitive styles. This study aims to describe students' critical thinking skills reflective and impulsive cognitive style, through Means Ends Analysis (MEA) model using visual media. The subjects of this study are the students of class VII consisting of 9 students of reflective cognitive style and 9 students of cognitive impulsive style in MTs Al-Asyhar Karangagung on biology study materials, environmental pollution subject. The cognitive style data was obtained through the Matching Familiar Figures Test (MFFT) test developed by Warli (2010). Further data on students' critical thinking were analyzed using non-parametric statistical analysis techniques with Mann Withney test. The results of this study indicate that there is no difference in the critical way of thinking of children who have a reflective and impulsive cognitive style. The conclusion shows that there is no difference in the way of critical thinking between students who have reflective cognitive style and who have impulsive cognitive style in the biology lesson through Means And Analysis (MEA) model using visual media.